Job engagement as the mediator on the relationship between leadership styles, organizational structure, and organizational performance - Ali, Khan Sarfaraz (2019)
The aim of this research is to investigate the relationship between leadership styles (i.e. transformational, transactional, and passive avoidant), organizational structure and organizational performance through the mediating role of job engagement in government-owned mobile phone company in Bangladesh. The study adopted the survey method for data collection and a total of 213 questionnaires were analyzed giving a response rate of 38.31 percent. This study used convenience sampling for sample selection. The respondents of the study were from the mid-level position e.g. senior executive, assistant manager, deputy manager, manager, and deputy general manager of Teletalk mobile phone company. The collected data were analyzed using SPSS version 20, and Partial Least Squares-Structural Equation Modeling (PLS-SEM) was used to test the study hypotheses. With regard to leadership styles, the study revealed that the relationship between transformational leadership style and organizational performance is statistically significant; whereas, the relationship between transactional and passive-avoidant leadership style with organizational performance is not significant. Similarly, the relationship between transformational leadership style and job engagement is significant; but the relationship between transactional and passive-avoidant leadership style with job engagement is not significant. Relating to organizational structure, the relationship between organizational structure with organizational performance and job engagement is found statistically significant. Job engagement is also significant with organizational performance. In terms of mediation effects, job engagement mediates the relationship between transformational, passive-avoidant leadership style and organizational structure with organizational performance partially, while the relationship between transactional leadership style and organizational performance is fully mediated by job engagement. Finally, the study implications, limitations as well suggestions are discussed accordingly.